Linking Green Hrm, Ethical Leadership, And Organizational Culture to Sustainable Employee Performance: A Commitment-Based Mediation Model - Ismail Ludin; Irman Ramdhan Fauzi; Muhammad Meki Munawar; Riski Wisnu Prakoso; Pardi Setiawan; Betharia Efriani (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
The Serang City Environmental Agency is a government institution that has the function and responsibility of maintaining environmental sustainability caused by human activities, both individually and collectively. The inquiry's purport resides in scrutinizing the modulatory effects of verdant human resource management, ethical stewardship, and corporate ethos upon organizational fealty, which in turn impinges upon perdurable productivity. A causal paradigm underpinned by quantitative modalities governed this research. Structural Equation Modeling-Partial Least Squares (SEM-PLS) facilitated data adjudication. Stratified aleatory sampling procured 100 respondents for the cohort. Verdant HRM stratagems were discerned to augment organizational allegiance, albeit sans direct incidence upon sustainable laborer efficacy. Ethical leadership substantially fortified both fealty and perdurable performance. Analogously, corporate ethos exerted propitious sway upon employee devotion, yet proffered no succor for sustained accomplishment. Ergo, organizational commitment was evinced as the pivotal moderator traversing verdant HRM, ethical leadership, corporate ethos, and laborer performance nexuses.